Peran Kegiatan “Tarsus” di Desa Pakulaut dalam Upaya Mendukung Gerakan Literasi Nasional - Ifada, Iqbal; Ansoriyah, Siti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Tarsus (Tarawih Khusus) is the name of an activity program from Pakulaut Village to increase community literacy. Many efforts have been taken to foster literacy. One of them is through efforts to implement 6 basic literacies carried out in Tarsus Pakulalut activities to generate the spirit of literacy, including literacy, numeracy, science, financial, digital, and also cultural and civic literacy. The purpose of this study is to explain the function of Tarsus Pakulaut activities associated with the 6 basic literacies. This research applies a descriptive approach using qualitative research methods. In this study, data triangulation is conducted by utilizing observation techniques, documentation, and interviews with Tarsus Pakulaut activity coaches and also Tarsus Pakulaut member communities. The results showed the role and support of Tarsus activities for the 6 basic literacies, among others: Village youth who provide Islamic material, breaking the fast with the Tarsus Pakulaut congregation, Tarsus Pakulaut Islamic Quiz Competition, making social media both Instagram, Facebook and also websites, Tarsus Pakulaut's Yuk Sedekah activity (Almsgiving activities for Tarsus), and finally the Nasyid Creation Competition (Islamic singing) and also the Tarsus Pakulaut Takbir Parade.————————————————————————————————Tarsus (Tarawih Khusus) merupakan nama program kegiatan dari Desa Pakulaut dalam meningkatkan literasi masyarakat. Banyak upaya yang dilakukan untuk memajukan literasi, salah satunya melalui implementasi 6 literasi dasar yang dilakukan dalam kegiatan Tarsus Pakulaut untuk mengembangkan semangat literasi, termasuk literasi bahasa, numerasi, sains, keuangan, digital, serta literasi budaya dan kewargaan. Tujuan dari penelitian ini adalah untuk menjelaskan fungsi kegiatan Tarsus Pakulaut yang terkait dengan 6 literasi dasar. Penelitian ini menggunakan pendekatan deskriptif dengan metode penelitian kualitatif. Dalam penelitian ini, triangulasi data dilakukan melalui teknik observasi, dokumentasi, dan wawancara dengan pembina kegiatan Tarsus Pakulaut dan juga anggota komunitas Tarsus Pakulaut. Hasil penelitian menunjukkan peran dan dukungan kegiatan Tarsus Pakulaut terhadap 6 literasi dasar, antara lain: pemuda desa yang menyediakan materi keislaman, buka bersama dengan jamaah Tarsus Pakulaut, Kompetisi Kuis Islami Tarsus Pakulaut, penggunaan media sosial seperti Instagram, Facebook, dan juga website resmi, kegiatan